Legal Issues of Cross-Border Data Transfer in the Era of Digital Government - G. Bolatbekkyzy (Journal of Digital Technologies and Law, 2024)
Objective: to identify the main legal factors of cross-border data exchange in the context of digital technology proliferation and government digitalization, including legal guarantees, security issues, cybersecurity risks, approaches to regulating and improving the efficiency of data management in various jurisdictions.Methods: the study relies on synthesis and critical analysis of various aspects of the stated problem, including analysis of primary and secondary sources. By the example of the regulatory policies of China, the US, the EU and EAEU member states, different approaches regarding the restriction or encouragement of free cross-border data transfer are compared. A comprehensive meta-analysis and literature assessment provided insights into the methods used for data protection in different jurisdictions and allowed outlining the framework and directions of the public policy required for effective cross-jurisdictional data transfer.Results: the main challenges associated with cross-border data transfer in the context of digital technology proliferation and government digitalization, such as growing inequalities in digital development, legal uncertainties, privacy and cybersecurity, etc., were identified. The legal framework of cross-border data transfer in the context of government digitalization and its implementation were analyzed. It contributed to the search for ways to improve the government efficiency in the context of transnational data transfer, including rendering services and promoting openness and public participation.Scientific novelty: based on the analysis of various jurisdictions’ approaches to legal, security and sovereignty issues caused by transnational data transfer, the author reveals the role and applicability of international law, as well as the unique challenges arising in the member states of the Eurasian Economic Union on the way to the formation of transboundary trust space.Practical significance: the study of these issues may help various public agencies, first of all, governmental and legislative bodies to the elaborate well-targeted political and legal decisions, aimed at achieving a balance between data availability and data security, between the effectiveness of public administration and respect for the human rights. The results obtained will also be of importance for other subjects of relations in cross-border data transfer and regulation of these relations.